THE IMPORTANCE OF LANGUAGE LEARNING STRATEGIES IN TEACHING ENGLISH TO TEENAGERS - Abdurakhmanova Mokhina (Journal of new century innovations, 2023)
ANNOTATION. Topicality of the course paper: In this coursework we should explain the importance of language learning strategies in teaching english to teenagers. So firstly we must know what is the importance of language learning strategies and how we can teach english to teenagers perfectly with this strategies. We should find out are there teenafers' some abilities or not to learn english. We should make clear how we can teach them in a simple way, how we can encourage and how we can motivate them.